Gradient‐echo EPI using a high‐degree shim insert coil at 7 T: Implications for BOLD fMRI. Issue 5 (1st December 2016) - Kim, Tae; Lee, Yoojin; Zhao, Tiejun; Hetherington, Hoby P.; Pan, Jullie W.
Abstract : Purpose: To quantitatively assess the effects of high degree and order (1 st –4 th+ ) relative to 1 st –2 nd degree B 0 shimming at 7 Tesla (T) on gradient‐echo echo planar imaging (GE‐EPI) and blood‐oxygen‐level dependent (BOLD) activation. Methods: Simulations and GE‐EPI were performed at (2mm) 3 and (3mm) 3 resolution, evaluating the temporal signal‐to‐noise ratio (tSNR), transverse relaxivity ( R 2 * ), BOLD % signal change and activated pixel counts in a breath‐hold task. Results: Comparing the 1 st –4 th+ degree with 1 st –2 nd degree shimmed B 0 maps generated spatially varying regions of Δ | B 0 | = | B 0 1 − 2 | − | B 0 1 − 4 + | . As binned in 10‐Hz intervals, the two center Δ| B 0 | (±10 Hz) bins maintained the B 0 offset of 48.6% of gray‐matter pixels. In the positive Δ| B 0 | bins greater than 10 Hz, the 1 st –4 th+ degree shimming improved the B 0 offset in 41.1%; in negative Δ| B 0 | bins less than −10 Hz, the offset worsened in 10.2% of the pixels. In the positive Δ| B 0 | bins, we found variable but significant increases in BOLD sensitivity; the negative Δ| B 0 | bins showed significant decreases. In the breath‐hold studies, positive bins showed significantly increased activated pixel numbers (+5–29%), whereas negative bins showed −18 to 0% decline. Conclusion: 1 st –4 th+ degree shimming maintained B 0 homogeneity over central brain regions while improving most of the other regions, including the inferior frontal lobe. Magn Reson Med 78:1734–1745, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.